Attosecond electronic timing with rising edges of photocurrent pulses - Minji Hyun (Nature Portfolio, 2020)
For edge-sensitive timing applications, the edge jitter of electrical pulses is important. Here, the authors report on very low rising edge jitter extracted from an optical frequency comb and explore the best condition for low jitter by minimizing the amplitude-to-timing conversion in photodiodes.